The Roman cremation burials of Encosta de Sant’Ana (Lisbon) - Gonçalves, David (2010)
Excavations of a Roman cemetery at Encosta de Sant’Ana in Lisbon uncovered a small number of cremation burials. Information about cremation practices during this particular period comes mostly from the writings of classical authors such as Pliny or Cicero. Opportunities to confirm their descriptions in Portugal by direct observation in the archaeological record have been rare. Therefore, the burials from Encosta de Sant’Ana offer the chance to add new knowledge to the picture obtained from faunal and human remains and the material culture itself. A bioarchaeological approach was adopted in order to infer the funerary behaviour of the inhabitants of Olisipo, Roman Lisbon, through their burned skeletal remains. In addition, a new frame of reference was developed to assist in the analysis of bone weight of the urned cremations. These allowed the reconstruction of funerary rituals and cremation practices.